Searching the Damaged Outgoing Feeder in Networks with Insulated Neutral by Phase-to-ground Fault - Sivokobylenko, Vitaliy; Kuzmenko, Dmitriy (Electrical, Control and Communication Engineering, 2010)
The method of searching the damaged feeder was improved by alternate disconnecting of feeder circuit-breakers, which allow to enlarge reliability of the systems of power supply by diminishing the number of multiple earth fault in electric network. Diminishing the number of multiple earth faults is attained by exception of switching overvoltage, because commutations of feeder circuit-breakers are carrying out when shunting circuit breaker is closed. The detection of damage in the feeder, when this method is used, is produced on the change of phase of current in the circuit of shunting circuit breaker after disconnecting of circuit-breaker of this feeder.